Screening of watermelon genotypes for resistance to mosaic disease under hot arid conditions of Rajasthan (Indian Journal of Arid Horticulture, 2013)
Mosaic disease is one of the most important diseases in the production of watermelon under arid and semi-arid  regions of India. Field trials were conducted to screen 13 watermelon/mateera genotypes viz., RW-177-3, RW-187-2, GP 20, GP- 35, GP- 42, Thar Manak, AHW- 19, AHW- 65, Asahi Yamato, Sugar Baby, Arka Manik, Bikaner Local-1 and  Barmer Local-1 for resistance against mosaic disease with normal cultivation practices during summer 2011 and 2012 at  Plant Pathology Block of Central Institute For Arid Horticulture, Bikaner under field conditions. Resistant genotypes were  categorized on the basis of disease incidence. Among 13 watermelon/mateera genotypes, none was found immune against  disease. One variety 'Asahi Yamato' showed resistance with less than 10.0% disease incidence, ten genotypes were  categorized as moderately resistant ranging from 10.1 to 25.0% disease incidence and two genotypes such as RW-177-3 and  GP- 20 having more than 25.0% disease incidence proved susceptible against mosaic disease.
Keywords: Watermelon; genotypes; mosaic disease; resistance